REFORMASI SISTEM PENSIUN PASCA UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA GUNA MEWUJUDKAN KESEJAHTERAAN BAGI PEGAWAI NEGERI SIPIL - Fiqi Fatichadiasty (SASI, 2020)
Pension is a right that is obtained by a civil servant. Civil servants with the aim of improving welfare. This is in accordance with Law Number 43 of 1999 concerning Personnel Fundamentals, Article 32 which states to increase the excitement that is carried out by seeking the welfare efforts of Civil Servants, welfare businesses that contain remuneration programs. However, there are still some shortcomings in one of the retirement age limits that have not been clearly stipulated in a regulation. With this research, it is expected to discuss a complete and in-depth acceptance of the substantive revenue from the Civil Servants Retirement Age Limit and also changes in the income system stated by the government. The methodology used in this study consists of a qualitative description and study of the process of reforming the civil service recipient system, which is distributed in terms of legal basis. After the enactment of Law Number 5 of 2014 concerning State Civil Apparatus.